2013
DOI: 10.1186/1471-2164-14-560
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential RNAi targets in grain aphid (Sitobion avenae F.) based on transcriptome profiling of its alimentary canal after feeding on wheat plants

Abstract: BackgroundThe grain aphid (Sitobion avenae F.) is a major agricultural pest which causes significant yield losses of wheat in China, Europe and North America annually. Transcriptome profiling of the grain aphid alimentary canal after feeding on wheat plants could provide comprehensive gene expression information involved in feeding, ingestion and digestion. Furthermore, selection of aphid-specific RNAi target genes would be essential for utilizing a plant-mediated RNAi strategy to control aphids via a non-toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 45 publications
3
65
1
1
Order By: Relevance
“…Based on this observation 5 major exotic unigenes explored via transcriptomic profiling of wheat aphids were selected (Zhang et al, 2013). These unigenes were confirmed in our local aphid strains such as M. rosae, R. maidis, S. avenae, T. aurantii) feeding on C. sinensis, R. indica, S. melongen, Z. mays and T. aestivum.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Based on this observation 5 major exotic unigenes explored via transcriptomic profiling of wheat aphids were selected (Zhang et al, 2013). These unigenes were confirmed in our local aphid strains such as M. rosae, R. maidis, S. avenae, T. aurantii) feeding on C. sinensis, R. indica, S. melongen, Z. mays and T. aestivum.…”
Section: Resultsmentioning
confidence: 62%
“…Secondly artificial feed also because high mortality within 24 hours comparable to microinjection and low dosage of the construct in artificial diet was found to be efficient for aphid mortality. The 5 unigene sequences selected will be used for RNAi based assay by producing transgenic tobacco followed by transgenic corn and wheat (Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that a range of insect cells possess RNAi activity (Roether and Meister 2011;Terenius et al 2011). With the purpose of identifying target genes for silencing in aphid gut, Zhang et al (2013) performed RNA sequencing on the alimentary canals of grain aphids before and after feeding on wheat plants. They identified 16 genes that were significantly up or downregulated upon feeding and suggested these were good targets for RNAi insect control strategies.…”
Section: Strategies For Insect Resistancementioning
confidence: 99%